Analisis Faktor yang Memengaruhi IPM dan Kemiskinan di Indonesia Tahun 2021 - Sari, Nurul Puspita (The Indonesian Journal of Social Studies, 2023)
Poverty is a social fact that has many meanings that vary based on place and time, poverty can be described in various ways as well as methods of alleviation. People as the central point of development should not only be a tool but also a goal of development. One method of poverty alleviation is through improving human quality through increasing Human Development Index. The purpose of this study is to see how the influence of health, education, economy and employment factors affects increasing Human Development Index and reducing poverty. The method used is path analysis with the variables Old School,School Percentage, Life Expectancy, Regional Income and Dependency Ratio. Based on the research that poverty in Indonesia is influenced directly or indirectly by HLS, HDI, PAD and DR. Human Development Index is the variable that has the greatest influence on poverty in Indonesia.